2023
DOI: 10.2196/43695
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mobile App (PIMPmyHospital) in Reducing Therapeutic Turnaround Times in an Emergency Department: Protocol for a Pre- and Posttest Study

Abstract: Background Delays in reviewing issued laboratory results in emergency departments (EDs) can adversely affect efficiency and quality of care. One opportunity to improve therapeutic turnaround time could be to provide real-time access to laboratory results on mobile devices available to every caregiver. We developed a mobile app named “Patients In My Pocket in my Hospital” (PIMPmyHospital) to help ED caregivers automatically obtain and share relevant information about the patients they care for inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that remote monitoring systems demonstrate the potential to enhance patient self-management and health care efficiency [ 1 ]. For instance, the iGetBetter system strengthens the connection between patients with heart failure and their medical teams [ 2 ], while the PIMPmy Hospital app is expected to optimize laboratory result access processes in pediatric emergency rooms [ 3 ]. In their study, McCrabb et al [ 4 ] conducted a web-based cross-sectional survey of patients with orthopedic trauma from 2 public hospitals in New South Wales, Australia, and found that more than half of the respondents expressed interest in using the internet to promote their health.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that remote monitoring systems demonstrate the potential to enhance patient self-management and health care efficiency [ 1 ]. For instance, the iGetBetter system strengthens the connection between patients with heart failure and their medical teams [ 2 ], while the PIMPmy Hospital app is expected to optimize laboratory result access processes in pediatric emergency rooms [ 3 ]. In their study, McCrabb et al [ 4 ] conducted a web-based cross-sectional survey of patients with orthopedic trauma from 2 public hospitals in New South Wales, Australia, and found that more than half of the respondents expressed interest in using the internet to promote their health.…”
Section: Introductionmentioning
confidence: 99%